ANALISIS PENGARUH PENANAMAN MODAL ASING dan PENANANAMAN MODAL DALAM NEGERI TERHADAP PERTUMBUHAN EKONOMI : di Jawa Tengah 1990 – 2010 - Nur Mustar Muazi; Fitrie Arianti (Diponegoro Journal of Economics, 2013)
The purpose of development except to create a high economy growth, are also reduces the level of poverty, unemployment, and income disparity. Even though not being the best indicator, Gross Domestic Regional Product (GDRP) was considered can give a good reflection of social welfare because it could indicating the economy growth. Some crucial things which have been playing an important part in influencing the GDRP of Central Java Province are domestic investment (PMDN) and foreign investment (PMA) which are invested on that province. The purpose of this research is to analyze the influence of domestic investment (PMDN) and foreign investment (PMA) toward GDRP of Central Java Province during the period of 1990-2010 were motivated by the fact that the growth of investment in Central Java tends to negative during the observation period, and it indicates that the investment and economy growth in Central Java related negative. This research used econometric model approach to co-integration and dynamic model approaches ECM (Error Correction Model) for methods of analysis. And it aims to theoretically and empirically analyze whether the resulting model is consistent with the theory or not.The results of multiple linear regression to estimate ECM shows that domestic investment (PMDN) and foreign investment (PMA) have influences toward GDRP in Central Java. In the short-term and long-term shows that domestic and foreign variable have positive and significant effect on the value of GDRP in Central Java.